Brinjal Identification and Classification Using Multiclass Support Vector Machine Algorithm. - Reka; R., Anitha (Proteus, 2022)
Brinjal is the most popular tropical vegetable in agriculture. It is an essential process We would like to encourage for separating various types of brinjals. Since it is grown in large quantities which varies in size, form and color. In countries such as U.S.A, Asian and many African countries this is the major vegetable crop. Estimation of brinjal cultivation is projected to be 32 million tons worldwide. Farmer's most popular approach for identifying the form of brinjal is to examine the plant or vegetable with their previous experience with plant development. To classify and recognize the brinjal types, the GLCM feature extraction technique is used with MSVM classifier. The most important factor in the production of automated brinjal sorting machines is to minimize the human labor and save time. This algorithm aids in improving the classification accuracy and performance. It is necessary to utilize the most advanced image processing technique to classify the brinjals.